Adolescents’ premarital sexual behaviour: the roles of peer pressure, socio-economic status and parent-child relationship (2019)
In recent times, there are records of prevalence of mortality among adolescents owing to sexually transmitted infections (STIs), unwanted pregnancy, abortion, induced pregnancy and related issues. This disastrous situation is traceable to adolescents' engagement in premarital sexual behaviour. This motivated an examination of peer pressure, socio-economic status, and parent-child relationship as correlates of adolescents’ premarital sexual behaviour. The study adopted descriptive survey design of the ex-post facto type. Three hundred adolescents were randomly sampled from secondary schools in Ibadan South-East Local Government Area of Oyo State, Nigeria. Data were collected using reliable instruments (Premarital Sexual Behaviour Scale a-0.87; Parental-Child Relationship Scale a =0.77; Socio-economic Status Scale a =0.73; Peer Influence Scale a = 0.75). Three research questions were raised and answered at 0.05 level of significance using Pearson's Product Moment Correlation and Multiple Regression Analysis. The study discovered that peer pressure (r = .883, P<0.01), parental socio-economic status (r = -.203, P<0.01) and parent-child relationship (r = -.536, P<0.01) significantly correlated with adolescents' premarital sexual behaviour. Among others, it was recommended that parents should build a healthy relationship with adolescents so as to be able to monitor and guide them against premarital sexual behaviour while school administrators and policy makers should intensify the teaching of sex education in secondary schools in order to acquaint adolescents with the dangers inherent in premarital sexual behaviour